Determination of Relative Frequency of HBS Ag, HCV and HIV Antibodies Serum Markers among Admitted Intravenous Drug Users in Infectious Disease Ward of Razi Hospital in Ahvaz, 2004-2005 - Abdolrasool Nikkhooy; Mohammad Nikkhooy; Nasrin Saadati (Shahid Sadoughi University of Medical Sciences, 2012)
Introduction: Intravenous drug users as a serious health problem in communities have economical and social effects as well as health and hygienic complications. Viral infections may be transmitted through drug injection by shared syringes among users. The aim of this study has been to determine the relative frequency of HBV, HCV and HIV infection's markers as epidemiological data in Ahvaz. Materials & Methods: This retrospective cross sectional study was conducted on IV drug users (IVDUs) who were admitted in infectious diseases ward of Razi Ahvaz Hospital in 2004-2005. The collected data of serum markers of these patients were coded, and statistical analyses were conducted. Results: 1890 patients were evaluated and 258 patients were IVDUs (14.6%). 154 patients (59.98%) were tested for anti HCV-Ab of whom 65 patients were HCV-Ab positive (42.2%). 205 patients (79.45%) were tested for anti HIV-Ab of whom 38 patients were HIV-Ab positive (18.53%). 67 patients (25.96%) were tested for HBs-Ag of whom 15 patients were HBs-Ag positive (22.67%). 12 patients (4.65%) were tested for anti HBc-Ab of whom 8 patients were HBc-Ab positive (66.66%). Conclusion: In this study, high infection rate relates to different causes such as increasing consumes of opium substances and recent differences in fumigated opium substances pattern toward injecting drug use in society level, which increases the prevalence of these infections, The present study determined some critical information about the prevalence of serum markers HBS Ag, HCV and HIV antibodies among intravenous drug users in southwestern of Iran.